The chemical composition of different edible locations (central and edge muscles) of flat fish (Lepidorhombus whiffiagonis). (18th September 2017) - Barbosa, Roberta G.; Trigo, Marcos; Prego, Ricardo; Fett, Roseane; Aubourg, Santiago P.
Summary: The chemical composition of the different edible locations (central and edge muscles) of a flat fish (megrim, Lepidorhombus whiffiagonis ) was comparatively analysed at both body sides. Higher moisture and lower lipid contents were obtained in central muscles than in edge ones. Edge sites showed higher triacylglycerols and sterols contents and lower mean phospholipids values than central muscles. A higher α‐tocopherol presence was observed in the lipid fraction of central muscles than in the edge ones. For both fish sides, fatty acid (FA) analysis showed lower monounsaturated FA and higher polyunsaturated FA contents and ω3/ω6 ratios in central muscles. Presence of essential elements (Co, Cu, Mn, Se, Zn) did not provide differences among sites considered. Concerning toxic elements, As content showed greater levels in central muscles than in their corresponding edge sites for both fish sides, upper zones showed higher mean scores in As, Cd, Cr, Hg, Ni, Pb and V. Abstract : Comparative study of two‐side composition of megrim muscle.